Voxel-wise radiogenomic mapping of tumor location with key molecular alterations in patients with glioma. Issue 11 (9th August 2018) - Tejada Neyra, Miguel Angel; Neuberger, Ulf; Reinhardt, Annekathrin; Brugnara, Gianluca; Bonekamp, David; Sill, Martin; Wick, Antje; Jones, David T W; Radbruch, Alexander; Unterberg, Andreas; Debus, Jürgen; Heiland, Sabine; et al.
Abstract: Background: This study aims to evaluate the impact of tumor location on key molecular alterations on a single voxel level in patients with newly diagnosed glioma. Methods: A consecutive series of n = 237 patients with newly diagnosed glioblastoma and n = 131 patients with lower-grade glioma was analyzed. Volumetric tumor segmentation was performed on preoperative MRI with a semi-automated approach and images were registered to the standard Montreal Neurological Institute 152 space. Using a voxel-based lesion symptom mapping (VLSM) analysis, we identified specific brain regions that were associated with tumor-specific molecular alterations. We assessed a predefined set of n = 17 molecular characteristics in the glioblastoma cohort and n = 2 molecular characteristics in the lower-grade glioma cohort. Permutation adjustment ( n = 1000 iterations) was used to correct for multiple testing, and voxel t -values that were greater than the t -value in >95% of the permutations were retained in the VLSM results (α = 0.05, power > 0.8). Results: Tumor location predilection for isocitrate dehydrogenase ( IDH ) mutant tumors was found in both glioblastoma and lower-grade glioma cohorts, each showing a concordant predominance in the frontal lobe adjacent to the rostral extension of the lateral ventricles (permutation-adjusted P = 0.021 for the glioblastoma and 0.013 for the lower-grade glioma cohort). Apart from that, the VLSM analysis did not reveal a significant association of the tumor location with any other key molecular alteration in both cohorts (permutation-adjusted P > 0.05 each). Conclusion: Our study highlights the unique properties of IDH mutations and underpins the hypothesis that the rostral extension of the lateral ventricles is a potential location for the cell of origin in IDH -mutant gliomas.